THE COMMUNICATIVE LANGUAGE TEACHING (CLT) APPROACH IN MODERN TESOL (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
The article provides a comprehensive analysis of the Communicative Language Teaching (CLT) approach within modern TESOL (Teaching English to Speakers of Other Languages). It traces the evolution of CLT, comparing it with older methods such as the Grammar Translation and Audio-lingual methods. The paper highlights the strengths of CLT, including its emphasis on real-world language use, interactive and learner-centered teaching, and its adaptability across various proficiency levels and learner contexts. However, it also discusses the limitations of CLT, such as its neglect of explicit grammar instruction and the challenges it presents in large classes or with students unfamiliar with communicative methods. Additionally, the article explores how CLT has adapted to contemporary technological advancements, integrating digital tools and online platforms to enhance language learning and communication. Ultimately, the paper underscores CLT’s significance in shaping modern language education while acknowledging the need for a balanced approach that incorporates both communicative competence and grammatical accuracy.